ミズホ キチ ノ ヒョウショウ ヒョウメン ニオケル ショウカ ト ギョウケツ ダイ1カイ ナンキョク キスイケン シンポジウム - 藤井, 理行; フジイ, ヨシユキ; FUJII, Yoshiyuki (国立極地研究所, 1979)
P(論文) みずほ基地の氷床表面における昇華量と凝結量を,1977年2月から1978年1月の期間について,蒸発皿法・バルク公式・雪尺による3つの異なった方法を用いて推定した.これらの方法で求めた1977年～1978年の夏期間の日昇華量は,満足できる一致を示した.特に週平均昇華量はよく一致した.凝結は4月中旬から9月中旬の5ヵ月間卓越し,その他の7ヵ月間は昇華が卓越するという明りょうな季節変化が認められた.年間凝結量,昇華量はそれぞれ0.19g/cm^2,4.92g/cm^2となり,昇華の卓越が著しい.日昇華量のピークは,日射量がピークを示した12月22日に,92mg/cm^2の値となった.これらの結果は,斜面下降風領域の夏期の昇華が,氷床表面の熱収支・質量収支に大きな役割を果していることを示唆している. Sublimation and condensation were estimated by three different methods, that is, atmometer, bulk formula and stake methods, at Mizuho Station from February 1977 to January 1978. The comparison of the three different methods of obtaining the sublimation rate in the summer of 1977-1978 showed a satisfactory agreement, especially in the weekly values. Condensation prevails in the period of five months from the middle of April to the middle of September and sublimation in the remainder seven months. The daily amount of sublimation showed its maximum, 92 mg/cm^2 on December 22 when the solar radiation was maximum. The annual amounts of sublimation and condensation are estimated to be 4.92 g/cm^2 and 0.19 g/cm^2 respectively. The present study implies that sublimation plays an important role in the heat and mass exchanges at the surface and in the metamorphism of surface texture. departmental bulletin paper